Trends of organizational branding strategies- systematic review and research agendas - Debebe Alemu; Shimelis Zewdie (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
Branding is among the activities that seek new ways to balance competition in the business environment to sustain organizational competitive advantage. Hence, this study aims to identify how the concept has been considered in the literature and its evolution in the marketing literature. To achieve the objectives of the systematic study review was conducted from 2010 to 2021 years and identified 98 articles. The collected data were documented in Microsoft Word and retained in Mendeley referencing software. The study revealed that brand and product management lacks conceptual clarity, which influences their measurement and subsequently their management. The review also demonstrates as economic, identity, consumer-based, personality, relational, community, cultural, and sensory approaches, respectively, are the respective evolutions of the concepts.